علاقة جودة الحياة بقلق الإمتحان لدى تلاميذ السنة الرابعة متوسط - ميهوب، وهيبة (جامعة الوادي university of Eloued, 2019)
الملخص:تهدف الد راسة الحالية إلى التعرف على طبيعة العلاقة بين جودة الحياة وقلق الامتحان لدى تلاميذ السنة الرابعة متوسط حيث تفترض الدراسة وجود علاقة بين جودة الحياة وقلق الامتحان لدى أفراد عينة البحث ولتحقيق هذا الهدف تم اعتماد المنهج الوصفي، وذلك باستخدام مقياس جودة الحياة الذي أعده منسي وكاظم (2006) وكذا مقياس قلق الامتحان الذي أعده عبد الناصر غربي (2015)، وتكونت عينة الدراسة من (70) تلميذ وتلميذة، تم اختيارهم بطريقة عشوائية من متوسطة "عياشي عمر الطاهر" بالوادي، و للإجابة عن تساؤلات الد راسة قمنا بجمع البيانات وتبويبها ثم اختبار الفرضيات باستخدام معامل الارتباط "بيرسون" و معامل "ألفاكرومباخ" وكذا اختبار "t test" لدلالة الفروق بين الجنسين، بالاستعانة بالحزمة الإحصائية ( SPSS ) فكانت النتائج على النحو التالي: 1- توجد علاقة ارتباطيه بين جودة الحياة و قلق الإمتحان لدى تلاميذ السنة الرابعة متوسط . 2 - توجد علاقة إرتباطية بين جودة الحياة و قلق الإستعدادللإمتحان لدى تلاميذ السنة الرابعة متوسط. 3 - توجد علاقة إرتباطية بين جودة الحياة و قلق أداء الإمتحان لدى تلاميذ السنة الرابعة متوسط. 4- لا توجد علاقة إرتباطية بين جودة الحياة و قلق إنتظار نتيجة الإمتحان لدى تلاميذ السنة الرابعة متوسط. 5-لا توجد فروق في جودة الحياة لدى تلاميذ السنة الرابعة متوسط تغزى لمتغير الجنس (ذكور/إناث). 6- توجد فروق في قلق الإمتحان لدى تلاميذ السنة الرابعة متوسط تغزى لمتغير الجنس (ذكور/إناث) . وبناء على النتائج المتوصل إليها تتبين ضرورة القيام بدراسات أكثر عمقا، وعلى عيناتأكبر، بهدف خفض المستويات المرتفعة من قلق الامتحان، وتحسين جودة الحياة لدى التلاميذ المتمدرسين. The Study Summary The current study aims to reveal the relationship between quality of life with the exam anxiety for students of the fourth year level where the study assumes a relationship between quality of life and exam anxiety of the members of the research sample and to achieve this goal the descriptive approach was adopted using the quality-of-life scale prepared by mansi and kazim As well as the scale of the test anxiety prepared by Abdel-Nasser Gharbi on a sample of 70 pupils were randomly selected from Ayashi Omar al-Tahir middle school in El-oued and to answer the questions of the study we collected data and then tested the hypotheses using Pearson correlation coefficient and Vickrumbach coefficient as well as test " t –test " to indicate gender differences by using The statistical package ( SPSS ) The results were as follows : 1. There is a correlation between quality of life and exam anxiety among students of the fourth year level . 2. There is a correlation between quality of life and anxiety preparing for the exam among the fourth year level students . 3. There is a correlation between quality of life and anxiety exam performance among the fourth year level students . 4. There is no correlation between quality of life and anxiety waiting for the exam result among the fourth year level pupils . 5. There is no statistically significant correlation in the quality of life among the fourth year level pupils of the female sex variable male . 6. There is a statistically significant relationship of the exam anxiety among the fourth year level pupils of the male sex variable female one . Based on the results achieved it Is necessary to conduct more in-depth studies and on larger samples in order to reduce the high levels of exam anxiety and improve the quality of life of the students enrolled .
دراسة ميدانية بمتوسطة عياشي عمر الطاهر بالوادي
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: قلق الإمتحان، جودة الحياة